Impact of the incorporation of date pit flour an underutilized biowaste in dough and its functional role as a fat replacer in biscuits. Issue 3 (19th January 2021) - Saeed, Syed Muhammad Ghufran; Urooj, Saman; Ali, Syed Arsalan; Ali, Rashida; Mobin, Lubna; Ahmed, Rahil; Sayeed, Syed Asad
Abstract: Date pit ( Phoenix dactylifera L.), an underutilized biowaste, is the major by‐product of the date processing industry. Date pits (DPs) are the naturally rich sources of several bioactive compounds that play a vital role in the prevention of the diseases. In the present study, the effect of date pit flour (DPF) as a fat replacer in biscuits at different concentrations (10, 20, 30, and 40% wt/wt) was explored. The proximate, functional, rheological, microstructural, phytochemical, antioxidant, nutritional, and sensory properties of the flour and the biscuits samples were evaluated. The results demonstrated that different ratios of DPF and wheat flour (WF) had high contents of ash, crude fibers, proteins, phytochemicals, and antioxidant activity in contrast to the commercial WF that showed lowest values for all the above components. It was observed that the inclusion of DPF (used in same percentage as fat replacer in biscuit formulation) in the WF alters dough rheology significantly. The gluten content of the flour blends decreased with the addition of DPF while the water absorption increased that interfere in the gluten development time, and it was increased from 1.67 min for control (without DPF) to 7 min for 40% DPF substitution. The scanning electron microscopy of biscuits dough elaborated after fat replacement at different levels showing that evenly distribution of starch granule was disrupted, and the gluten matrix was often ruptured. The total phenolic content (TPC) and total flavonoid content (TFC) increased from 18.56 to 451.60 mg GAE/100 gm of sample and 27.43 to 361.20 mg CE/100 g, respectively. Although, baking decreased the TPC, whereas TFC was increased as compared to the control, and similar results were observed for the antioxidant activity for other substituted biscuits. The crude fiber and protein contents of DPF‐WF biscuits were improved from 0.44% to 8.70% and 11.79 to 12.69%, respectively, Sensory and textural performance exhibited that the biscuits were acceptable after fat replacement up to 20% DPF. Based on this study, DPF may be suggested as an excellent natural fat replacer to be used in nutraceuticals and functional foods. Practical applications: The current approach enhances the economy of date processing industries by providing value to waste as date pits (DPs). Furthermore, it may be suggested that date pit flour (DPF) is a valuable food industry waste that may play highly beneficial role in producing bakery products of enhanced nutritional values at economical cost. The study had shown that certain compounds of DPF such as proteins, fibers, and phytochemicals which apart from being active and important nutrients may contribute to desirable functional properties by closed interactions at the molecular level between the components of major ingredients. The mixing process provides opportunities to form complexes from these interactions that further react during baking when a suitable thermal atmosphere is available. It seems that introducing DPF is a good discovery that has opened the wide door for numerous novel nutraceutical product development and simultaneously making use of food industry by‐products.